Study on spatial characteristics of coal seam water injection diffusion and fracture network flow patterns based on B-GFP fluorescent bacteria tracing - Dong XIAO; Suping PENG; Xuechen LI; Hailun HE (Meitan xuebao)
Identifying fracture development patterns in coal seams is critical for assessing seam permeability and the effectiveness of techniques like hydraulic fracturing. As mining depths increase, the complexity of fracture formation under the influence of in-situ stress and tectonic forces grows, limiting the accuracy of traditional detection methods in tracing fracture flow paths during hydraulic operations. This study introduces a novel biotracing technique, employing genetically modified green-blue fluorescent bacteria (B-GFP) that demonstrate strong adaptability to the coal seam environment and stable surface adsorption properties. The adsorption behavior of the fluorescent bacteria at various dilution ratios was systematically analyzed, along with their flow patterns within coal seam fractures. The findings provide a new method for evaluating the effectiveness of hydraulic interventions. The experiments revealed that bacterial solution diffusion in coal seams is influenced by both the organic metabolite content and fracture characteristics. At higher concentrations, the solution showed enhanced wettability, forming a bacteria-liquid two-phase film on the coal surface, causing the bacteria to cluster visibly. Conversely, at higher dilution ratios, the solution’s wettability decreased, and bacteria adhered to rough surfaces in a more dispersed manner, using their flagella. A 50-fold dilution was identified as the optimal condition for creating a uniform bacterial film, ensuring maximum tracer visibility. Furthermore, B-GFP fluorescent bacteria were able to adhere stably to pre-fractured coal samples, unaffected by fracture development or expansion, effectively marking through-going fractures, fracture networks, and semi-closed fractures. Using this biotracing technique, the hydraulic impact radius in the mining face was evaluated, showing that it accurately depicts the distribution of fractures and the spatial flow characteristics of injected water. The study found that the actual impact radius of coal seam water injection exceeds 4 m, suggesting borehole spacing could be extended to 8 m. These results provide valuable theoretical support and practical guidance for optimizing coal mine gas control and hydraulic techniques, with significant potential to enhance the efficiency of hydraulic operations.